2014
DOI: 10.1088/0031-9155/59/23/7419
|View full text |Cite
|
Sign up to set email alerts
|

Positron range in PET imaging: non-conventional isotopes

Abstract: In addition to conventional short-lived radionuclides, longer-lived isotopes are becoming increasingly important to positron emission tomography (PET). The longer half-life both allows for circumvention of the in-house production of radionuclides, and expands the spectrum of physiological processes amenable to PET imaging, including processes with prohibitively slow kinetics for investigation with short-lived radiotracers. However, many of these radionuclides emit 'high-energy' positrons and gamma rays which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 31 publications
0
45
0
2
Order By: Relevance
“…Furthermore, the β + energy of 52m Mn (2633 keV) is higher than that of 51 Mn. This results in a mean ß + range of 5.3 mm in tissue and, thus, in a correspondingly lower resolution of PET images. Additionally, 52m Mn decays partially via internal conversion to its ground state 52g Mn, leading to an increasing contamination with the longer‐living 52g Mn over time.…”
Section: Relevant Pet Radionuclides Of Manganese For Medical Imagingmentioning
confidence: 99%
“…Furthermore, the β + energy of 52m Mn (2633 keV) is higher than that of 51 Mn. This results in a mean ß + range of 5.3 mm in tissue and, thus, in a correspondingly lower resolution of PET images. Additionally, 52m Mn decays partially via internal conversion to its ground state 52g Mn, leading to an increasing contamination with the longer‐living 52g Mn over time.…”
Section: Relevant Pet Radionuclides Of Manganese For Medical Imagingmentioning
confidence: 99%
“…86 Y (14.7 h), 89 Zr (78.4 h), 64 Cu (12.7 h), etc. in recent years [3][4][5]. Among other, 64 Cu is one of the most promising isotopes for the PET usage because it possesses the smallest average energy of positrons, and its half-life allows delivery to local clinics [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The target amides 4 were finally obtained by gentle base treatment of the salts 4*HCl (SI p. [2][3][4][5][6]. It was found that choice of the base is crucial to obtain the amides 4: using of strong base like alkali lead to de-acylation instead of formation of target amino-amides.…”
Section: Introductionmentioning
confidence: 99%
“…First, when compared to 90 Y ( t 1/2 ~ 64.1 h), 86 Y possesses a shorter half-life (14.7 h), which can preclude imaging studies at later time points. In addition, 86 Y emits a relatively high-energy β + ( E mean = 640 keV), meaning that the positrons have a long mean-free path length ( R mean = 2.5 mm) compared to other popular positron-emitting radiometals such as 64 Cu ( E mean = 278.2 keV, R mean = 0.56 mm) and 89 Zr ( E mean =402.7 keV, R mean =1.27 mm) [11]. As a result of this higher β + energy and an abundance of gamma emissions (1077, 1153, 1854, 1921 keV), the image quality of 86 Y-PET scans is reported as being sub-optimal.…”
Section: Introductionmentioning
confidence: 99%